Plasma and intracellular pharmacokinetics of tenofovir disoproxil fumarate and emtricitabine in transgender women receiving feminizing hormone therapy. (17th February 2020) - Cirrincione, Lauren R; Podany, Anthony T; Havens, Joshua P; Bares, Sara H; Dyavar, Shetty Ravi; Gwon, Yeongjin; Johnson, Tanner M; Amoura, N Jean; Fletcher, Courtney V; Scarsi, Kimberly K
Abstract: Background: Transwomen have an increased risk of HIV acquisition compared with other adults. Drug–drug interactions between pre-exposure prophylaxis (PrEP) and gender-affirming therapy are cited as a reason for poor PrEP uptake among transwomen. We evaluated plasma tenofovir and emtricitabine pharmacokinetics and their active intracellular anabolites, tenofovir-diphosphate and emtricitabine-triphosphate, in transwomen receiving feminizing hormones. Methods: We enrolled HIV-negative transwomen (≥19 years) not receiving PrEP. Participants took oral tenofovir disoproxil fumarate/emtricitabine 300/200 mg daily for 14 days. Plasma was collected at 0 h (pre-dose), 0.5, 1, 2, 3, 4, 6, 8 and 12 h on day 14 post-tenofovir disoproxil fumarate/emtricitabine dose. The plasma AUC0–24 was calculated using the trapezoidal rule and compared with historical HIV-negative cisgender adults as geometric mean ratios (GMRs, 90% CI). Secondarily, tenofovir-diphosphate and emtricitabine-triphosphate from PBMCs collected at 0 h and 12 h were reported descriptively as geometric means (90% CI). Clinical trials registration: NCT03270969. Results: Among 15 transwomen (mean age 32 years), geometric mean tenofovir and emtricitabine plasma AUC0–24 were lower compared with controls: tenofovir, 2.10 versus 2.76 mg·h/L, GMR 0.76 (0.65–0.90), P =  0.01; emtricitabine, 9.15 versus 10.64 mg·h/L, GMR 0.86 (0.75–0.98), P =  0.07. Tenofovir-diphosphate and emtricitabine-triphosphate concentrations were higher than previously reported in the literature: 167.1 (146.6–190.5) fmol/10 6 cells and 15.4 (13.8–17.3) pmol/10 6 cells, respectively. Conclusions: We observed lower plasma tenofovir and emtricitabine concentrations in transwomen compared with historical cisgender adults, yet intracellular tenofovir-diphosphate and emtricitabine-triphosphate concentrations were higher than previously reported in PBMCs. Understanding the differences of PrEP pharmacokinetics in plasma and tissue compartments and the resultant impact on efficacy remains important for transwomen.